2001
DOI: 10.1152/jappl.2001.90.1.287
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular activation during sympathetic imbalance and its computational reconstruction

Abstract: We characterized the epicardial activation sequence during a norepinephrine (NE)-induced ventricular arrhythmia in anesthetized pigs and studied factors that modulated it. Subepicardial NE infusion caused the QRS complex to invert within a single beat (n = 35 animals, 101 observations), and the earliest epicardial activation consistently shifted to the randomly located infusion site (n = 14). This preceded right atrial activation, whereas the total ventricular epicardial activation time increased from 20 +/- 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 19 publications
1
34
2
Order By: Relevance
“…However, no difference in arrhythmia was observed [20]. Desflurane has been reported to cause ventricular arrhythmia by activating the sympathetic nervous system [21][22][23]. In the present study, we demonstrated a statistically significant increase in ventricular arrhythmia in the desflurane group during the first 24 hours after induction.…”
Section: Discussioncontrasting
confidence: 43%
“…However, no difference in arrhythmia was observed [20]. Desflurane has been reported to cause ventricular arrhythmia by activating the sympathetic nervous system [21][22][23]. In the present study, we demonstrated a statistically significant increase in ventricular arrhythmia in the desflurane group during the first 24 hours after induction.…”
Section: Discussioncontrasting
confidence: 43%
“…Anesthesia, intensive care, and surgical methods have been fully described previously 17 but are briefly summarized here. The investigation conformed to the Guide for the Care and Use of Laboratory Animals published by the US National Institutes of Health and was performed in accordance with the British Home Office license requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Epicardial activation mapping methods have been fully described previously 17 and are outlined schematically in Supplementary Figure S1. According to Haws and Lux, 21 ventricular epicardial activation times were computed for each epicardial electrogram with the steepest negative intrinsic deflection during the QRS complex (minimum dV/dt; see Figure S1A).…”
Section: Signal Analysis and Mappingmentioning
confidence: 99%
“…It can also directly raise the threshold for induction of ventricular fibrillation (72,73). Conditions associated with high vagal tone [e.g., exercise training (23) and gene transfer of neuronal nitric oxide (NO) synthase (nNOS) (25,71)] protect against mortality (20), while impaired vagal function has been demonstrated in both congestive cardiac failure (53) and hypertensive patients (56).…”
Section: Importance Of Autonomic Balance In Cardiovascular Diseasementioning
confidence: 99%